2004
DOI: 10.1016/j.jacc.2003.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of sildenafil in primary pulmonary hypertension

Abstract: Sildenafil significantly improves exercise tolerance, cardiac index, and QOL in patients with PPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(104 citation statements)
references
References 23 publications
3
95
0
4
Order By: Relevance
“…9,10 The cost of treatment with sildenafil 50 mg orally every 8 hours is CAN $6000 per year, which is 6 to 7 times cheaper than bosentan and 15 times cheaper than epoprostenol. The efficacy, simplicity, and potential cost savings of the oral PD-5 regimen support the need for larger trials and perhaps a head-to-head comparison of sildenafil and bosentan in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The cost of treatment with sildenafil 50 mg orally every 8 hours is CAN $6000 per year, which is 6 to 7 times cheaper than bosentan and 15 times cheaper than epoprostenol. The efficacy, simplicity, and potential cost savings of the oral PD-5 regimen support the need for larger trials and perhaps a head-to-head comparison of sildenafil and bosentan in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric studies have included patients with PHTN of various etiologies. Eight prospective studies, including a series of 87 children (ages ranging from infancy to 19 years) taking oral sildenafil, describe sildenafil's efficacy for improving hemodynamics and exercise tolerance [6,36,45,58,59,62,63,69]. Three of the prospective studies were randomized controlled trials involving pediatric patients with either persistent PHTN of the newborn or PHTN related to congenital heart disease [6,58,62].…”
Section: Sildenafil Efficacymentioning
confidence: 99%
“…Abdominal discomfort [69] Not otherwise described NR For this review, the incidence of each reported adverse event was calculated using the sum of all the patients receiving sildenafil in the studies and case reports. All the studies and case reports made reference to adverse events, often noting that no event was experienced, although few investigations specifically stated how or which adverse events were monitored.…”
Section: Sildenafil Safetymentioning
confidence: 99%
“…11,12 In adults with PH, sildenafil has improved survival rates, exhibited low toxicity, and is available as an enteral preparation that is more practical for long-term, outpatient therapy. [13][14][15][16][17][18][19][20] Early clinical experience indicates that sildenafil treatment may be efficacious for infants with BPD-PH, with evidence suggesting that sildenafil normalizes lung development and may improve outcomes. [21][22][23][24][25] However, practice patterns for sildenafil treatment in infants with BPD-PH have not been fully reported; these patterns include variables associated with exposure, timing of initiation, length of treatment, and interhospital variation in use.…”
mentioning
confidence: 99%